The self-employment of immigrants and natives in Sweden: To what extent is it the 'immigrant group' or the 'labour market context' that affects the self-employment of individuals in Sweden? - Henrik Ohlsson; Per Broomé; Pieter Bevelander (Institute for the Study of Labor (IZA), 2010)
Earlier studies on entrepreneurship and self-employment among immigrants call attention to the fact that also the market for self-employment or entrepreneurs consists of a supply and demand side as well as the interaction between these two. More recent research suggests that a mix of personal resources, the surrounding structural context of markets, competition and the current political and economic environment, all acting together are seen as determining factors affecting self-employment by immigrants. However, few studies have been able to quantify the importance of these different aspects that determine ethnic self-employment. The central aim of this paper is therefore, by using multilevel regression, to quantify the role the country of birth respectively labour market area plays for understanding individual differences in self-employment. Using register data on individuals for the year of 2007 for the entire Swedish population we have in this study a unique opportunity to quantify the relative importance of the self-employers embeddedness in the social and ethnic networks (country of birth) and the regional business and public regulatory framework (labour market areas) measured. Our results suggest that of the total variation in individual differences in self-employment can 14 % (men) respectively 16 % (women) be attributed to the ethnic group and the labour market area. Furthermore, the ethnical groups accounted for 70 % (men) and 78 % (women) of this higher level variance. These results show that the social and ethnical context (measured by country of birth) and the economic environment (measured by local labour market areas) played a minor role for understanding individual differences in self-employment. These results can have important implications when planning interventions or other actions focusing on self-employment. Focusing only on ethnical groups/labour market areas might be inefficient as approximately 85 % of the variation is not explained by ethnical groups/labour market areas. Instead more general approaches or interventions focusing on other groups that capture a larger part of the variation might be more efficient.
Keywords: J15; J21; L26; 330; Immigrants; self-employment; integration; entrepreneurship; multilevel logistic regression; Selbstständige; Unternehmer; Migranten; Bevölkerung; Regionaler Arbeitsmarkt; Schätzung; Schweden